A Middle Dorset dwelling in Trinity Bay, Newfoundland - LeBlanc, Sylvie (Études/Inuit/Studies, 2003)
AbstractThis paper describes a Middle Dorset dwelling in Trinity Bay Newfoundland. The dwelling features an extended flagstone pavement and a well defined lateral cooking area. The vast amount of refuse associated with the dwelling, as well as the radiocarbon dates ranging between 1880 and 1300 B.P., suggest that the house was occupied for a long period of time. The occupation of the dwelling was intense and complex and stratigraphic evidence points to at least five occupational or use episodes of the dwelling site.